Metode Analisis Kualitatif Senyawa Obat Methamphetamine pada Sampel Rambut - Bunga Nur Annisa; Lestari Mahardika Urbaningrum; Nena Vauziah Sary; Cantika Nurul Sa’adah; Audi Ichsani Aribowo; Christina Febiola Lubis (Jurnal Health Sains, 2022)
Methamphetamine (C10H15N) is a class two psychotropic, a stimulant that acts on the central nervous system, causing addiction when consumed. Hair as a part of the body is often used as an option to detect the presence of methamphetamine in the body. The advantage of hair is that the presence of a drug can last weeks to months. This review was done to see how methamphetamine was detected in hair samples. As a result, it is known that the detection of methamphetamine in hair samples can be carried out using the Solid Phase Extraction (SPE) method. The procedure begins with the preparation of Marquish reagent by mixing 37% formaldehyde with glacial acetic acid. The procedure continued with the preparation of hair samples by grinded 30-40 mg of hair and then washed it with ethanol. After that the sample was sonicated with various solvent systems at room temperature for 30 minutes. The last step is column extraction conducted by inserting the filtrate into the column basement membrane, the column was conditioned, then the sonicated analyte was added and carried out with dichloromethane: 4 ml, then eluted and the sample eluent obtained was identified using marquish reagent